2007
DOI: 10.1590/s0102-311x2007001100003
|View full text |Cite
|
Sign up to set email alerts
|

Mensuração do impacto dos problemas bucais sobre a qualidade de vida de crianças: aspectos conceituais e metodológicos

Abstract: Children are subject to oral health problems that can impact their own quality of life and that of their families. The need for measurements to assess the impact of oral health on children's quality of life has been emphasized, and questionnaires have been developed or adapted to this specific group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
28

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 52 publications
0
30
0
28
Order By: Relevance
“…However, it was not found studies to justify this finding. A study suggested that, although the use of secondary respondents is considered a possible alternative (8) , some aspects may be differently interpreted on the guardians' perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not found studies to justify this finding. A study suggested that, although the use of secondary respondents is considered a possible alternative (8) , some aspects may be differently interpreted on the guardians' perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there are two validated instruments to assess OHRQOL in children (5,6) , the Brazilian Early Childhood Oral Health Impact Scale (B-ECOHIS) (7) and the Scale Oral Health Outcomes for five-year-old children (SOHO-5) (6) . The B-ECOHIS is designated for children from 2 to 5 years old (5,8) and its use helps to increase knowledge about adverse oral conditions which affect children's quality of life (3,4,9,10) . Studies have shown that dental caries present negative impact on quality of life of children and their families, including nutrition aspects, behavioral oral symptoms and educational alterations (1,2,3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…A percepção de saúde e de doença varia conforme a capacidade cognitiva da criança, a qual se modifica de acordo com a idade, em função dos diferentes estágios de desenvolvimento emocional, social e de linguagem (TESCH et al, 2007). Uma estratégia para abordar as diferentes fases de desenvolvimento da criança é criar múltiplas formas de um mesmo instrumento para crianças, cada uma desenhada para diferentes faixas etárias.…”
Section: Avaliação Da Qualidade De Vida E Saúde Bucal Em Crianças E Aunclassified
“…The current literature [3-5] indicates that there is a strong association between enamel defects, prematurity and low birth weight [6]. …”
Section: Introductionmentioning
confidence: 99%